A plethora of rodents: Rattlesnake predators generate unanticipated patterns of venom resistance in a grassland ecosystem - Neil R. Balchan; Cara F. Smith; Stephen P. Mackessy (Toxicon: X, 2024)
Predation has the potential to impart strong selective pressures on organisms within their environments, resulting in adaptive changes in prey that minimize risk of predation. Pressures from venomous snakes present an exceptional challenge to prey, as venom represents a unique chemical arsenal evolutionarily tailored to incapacitate prey. In response, venom resistance has been detected in various snake prey species, and to varying degrees. This study analyzes venom resistance in an eastern Colorado grassland habitat, where the Prairie Rattlesnake (Crotalus viridis) and Desert Massasauga Rattlesnake (Sistrurus tergeminus edwardsii) co-occur with a suite of grassland rodents. We test for venom resistance across rodent and snake pairings using two geographically distant field sites to determine the role of 1) predation pressure and trophic ecology, and 2) sympatric and allopatric patterns of venom resistance. Resistance was measured using serum-based metalloproteinase inhibition assays to determine potential inhibition of proteolytic activity, augmented by median lethal dose (LD50) assays on rodent species to assess toxicity of crude venoms. Resistance is present in several rodent species, with strong resistance present in populations of Eastern Woodrat (Neotoma floridana), Ord's Kangaroo Rat (Dipodomys ordii), and Northern Grasshopper Mouse (Onychomys leucogaster). Resistance is less developed in other species, including the House Mouse (Mus musculus) and Plains Pocket Mouse (Perognathus flavescens). An unexpected differential is present, where Lincoln County Kangaroo Rats are highly resistant to venom of co-occurring Prairie Rattlesnakes yet are sensitive to an allopatric population of Prairie Rattlesnakes in Weld County. Lincoln Co. Northern Grasshopper Mice also demonstrate extremely elevated resistance to Weld Co. Prairie Rattlesnake venoms, and they may possess resistance mechanisms for myotoxin a, an abundant component of Weld Co. C. v viridis venoms. This study illustrates the complexity of venom resistance in biological communities that can exist when incorporating multiple species interactions. Future studies aimed at characterizing resistance mechanisms at the molecular level will provide a more detailed physiological context for understanding mechanisms by which resistance to venoms occurs.